Leukocyte transendothelial migration: A local affair. (2nd January 2017) - Schimmel, Lilian; Heemskerk, Niels; van Buul, Jaap D.
ABSTRACT: Inflammation is part of the complex biological response of body tissues to harmful stimuli, such as pathogens. It serves as a protective response that involves leukocytes, blood vessels and molecular mediators with the purpose to eliminate the initial cause of cell injury and to initiate tissue repair. Inflammation is tightly regulated by the body and is associated with transient crossing of leukocytes through the blood vessel wall, a process called transendothelial migration (TEM) or diapedesis. TEM is a close collaboration between leukocytes on one hand and the endothelium on the other. Limiting vascular leakage during TEM but also when the leukocyte has crossed the endothelium is essential for maintaining vascular homeostasis. Although many details have been uncovered during the recent years, the molecular mechanisms from the vascular part that drive TEM still shows significant gaps in our understanding. This review will focus on the local signals that are induced in the endothelium that regulate leukocyte TEM and simultaneous preservation of endothelial barrier function.